On Vocal Assemblages: From Edison to Miku. Issue 5 (2nd November 2018) - Prior, Nick
Abstract : For all its hermeneutic density the voice is a profoundly malleable object. By drawing our attention away from the 'grain' of the voice to networks of vocality, this article explores how modern mediations of the voice––from the microphone to auto-tune––illustrate its co-evolution with a history of non-human circuits and exchanges. The voice is categorized as an assemblage in the sense suggested by Deleuzian theoretical currents and actor network theory: a multi-scalar, human–non-human hybrid that emerges through nested constellations. Four vocal modalities––synthesis, deconstruction, auto-correlation, and simulation––are identified as integral to a modern history of vocal breaching experiments that transform what voices can be and how they are heard. The final part of the paper explores how these extensions play out in relation to the Japanese virtual singer, performer, and idol, Hatsune Miku. Miku's voice, it will be argued, is constituted at the intersection of crowd-sourcing, corporate investment and the algorithm. But it also illustrates the distributed ontology of all voices.